The Urgency of Parental Guidance for Youth Education in the Belajar Dari Rumah (BDR) Era - Neneng Yulda Sari; Wisroni Wisroni (Universitas Negeri Padang, 2020)
When Indonesia was hit by the Covid-19 pandemic, it has had a significant impact on the implementation of learning that was originally face-to-face, turned into distance-learning, or online. The implementation of the